Do you know this syndrome? Ichthyosis associated with neurological condition and alteration of hairs - Luciana Baptista Pereira; Neusa Yuriko Sakai Valente; Vanessa Barreto Rocha (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Trichothiodystrophy refers to a heterogeneous group of rare genetic diseases that affects neuroectodermal-derived tissues with multisystem involvement. The hallmark of these syndromes is the deficiency of sulfur in hair matrix proteins, leading to short and brittle hair. Few cases of this rare disorder have been published. The authors report a case of trichothiodystrophy in a male infant with ichthyosis, photosensitivity, spastic paraparesis, short stature, and neurologic and psychomotor retardation. Diagnosis was based on clinical and microscopic features of hair samples.